COMPUTER MODELING OF STRAINS ON PHASE BOUNDARIES IN DUCTILE CAST IRON AT HOT EXTRUSION - A. I. Pokrovsky; V. A. Kovtun; Т. V. Ryabchenko; I. Khrol (Литьë и металлургия)
The computer modeling of the strain distribution in the structure of ductile iron with ferrite-pearlite matrix and inclusions of spherical graphite dependence on increasing degree of deformation during direct hot extrusion was researched. Using a software system of finite-element analysis ANSYS the numerical values of the strains at the phase boundaries: ferrite-perlite, graphiteferrite and also inside the graphite inclusions were defined. The analysis of the strain distribution in the investigated structures was performed and local zones of increased strains were discovered. The results of modeling are compared with metallographic analysis and fracture patterns. The obtained results could be used in the prediction of fracture zones in the cast iron products.